2020
DOI: 10.1016/j.jcp.2020.109412
|View full text |Cite
|
Sign up to set email alerts
|

Pseudospectral computational methods for the time-dependent Dirac equation in static curved spaces

Abstract: Pseudospectral numerical schemes for solving the Dirac equation in general static curved space are derived using a pseudodifferential representation of the Dirac equation along with a simple Fourier-basis technique. Owing to the presence of non-constant coefficients in the curved space Dirac equation, convolution products usually appear when the Fourier transform is performed. The strategy based on pseudodifferential operators allows for efficient computations of these convolution products by using an ordinary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…The PML terms D x | jo jx,jy and D y | jo jx,jy , respectively, may be computed based on the PDEs ( 13) and (14). This approach leads one tõ…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The PML terms D x | jo jx,jy and D y | jo jx,jy , respectively, may be computed based on the PDEs ( 13) and (14). This approach leads one tõ…”
Section: Bmentioning
confidence: 99%
“…A review and comparison of BCs for quantum wave equations can be found in the literature [12]. Recently, this PML formulation has been joined with a pseudo-spectral method for the computation of the time-dependent Dirac equation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the problem of solving our very general Equation (10) without restricting the latter to the equatorial plane might be very important for other astrophysical applications besides neutron stars. We believe that the problem might very well be tackled by adapting to our case the existing numerical methods that have already proved fruitful elsewhere for solving such equations (see, e.g., the recent work [40] and the references therein).…”
Section: Refinements and Prospective Extensionsmentioning
confidence: 99%
“…For this purpose, the Pseudo-spectral Crank-Nicolson (PSCN) method introduced in Ref. [41,42] is used. Introducing a set of discrete times given by t n = t 0 + n∆t for n ∈ Z + , where t 0 is the initial time and ∆t is the time step, the Crank-Nicolson update is written as…”
Section: Numerical Schemesmentioning
confidence: 99%